Evaluation of the effects of spores and their heat-treated residues from different Bacillus strains on the initial growth of rice plants. Issue 2 (4th March 2019) - Seerat, Ali Yawar; Ookawa, Taiichiro; Kojima, Katsuhiro; Ohkama-Ohtsu, Naoko; Maeda, Masumi; Djedidi, Salem; Habibi, Safiullah; Sekimoto, Hitoshi; Abe, Akira; Yokoyama, Tadashi
ABSTRACT: This study evaluated the effects of the spores and their heat-treated residues from different strains of Bacillus species ( B. pumilus, B. altitudinis, and B. megaterium ) on the early growth of paddy rice cultivars, including Hitomebore (short-grain japonica rice), Takanari (high-yielding indica rice), and two new lines, TULK-143-6 and LTAT-29. The spores of seven Bacillus strains positively affected Hitomebore root growth, while, the root volume of TULK-143-6 with inoculation of B. pumilus TUAT1 and JM52, and root length and root surface area of LTAT-29 with inoculation of B. megaterium MAFF301694 were increased significantly. In contrast with Hitomebore, Takanari root growth was significantly inhibited by the spores of six Bacillus strains. Surprisingly, inoculations with the spore residues from all tested Bacillus strains increased the root dry weight of Hitomebore, with the effects of four bacterial strains being significant. Furthermore, there were more Bacillus spores than vegetative cells at different time points during the initial rice growth stage, and most plant samples mainly consisted of Bacillus spores. Thus, the spores of Bacillus species likely promote rice root development.